IDENTIFIKASI SENYAWA ANORGANIK NITRAT PADA AIR RUMAH TANGGA DI WILAYAH KERJA PUSKESMAS MIJEN, SEMARAMG - Kanti Ratnaningrum; Merry Tiyas Anggraini; Hera Vinandika Purwagumilar; Pudjiati Syarif (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2015)
Water consumed should be eligible physical, chemical, and bacteriological. Nitrite is the watersoluble chemical compound that can damage the health, including cause of diarrhea. The high incidence of diarrhea and not achieving the target of the coverage areas of environmental health in terms of supervision and control of water quality in Puskesmas Mijen, Semarang, it is necessary to research that aims to identify the nitrate values in water source at coverage ofPuskesmas Mijen, Semarang. A descriptive analytic study using systematic sampling methodwith estimate proportion formula. Sampling was carried out in 10 villages were included incoverage area of Puskesmas Mijen, Semarang. The examination nitrate levels in water isperformed in laboratory of Balai Laboratorium Kesehatan Semarang. From 36 water samplesanalyzed that the majority of water source in Puskesmas Mijen (97.2%) met the criteria forquality standards nitrate (10 mg/L). Ngadirgo water source is the only one of village does notappropriate the quality standard criteria of nitrate values (2.8%).